EURADOS intercomparison exercise on MC modelling for the in-vivo monitoring of AM-241 in skull phantoms (Part II and III). (August 2015) - Vrba, Tomas; Broggio, David; Caldeira, Margarida; Capello, Kevin; Fantínová, Karin; Franck, Didier; Gómez-Ros, Jose Maria; Hunt, John; Kinase, Sakae; Leone, Debora; Lombardo, Pasquale Alessandro; Manohari, Murugan; et al.
Abstract: An intercomparison on in-vivo monitoring for determination of Am-241 in three skull phantoms was launched by EURADOS in 2011. The project focused on measurement and estimation of the activity of Am-241 in the human skull. Three human skull phantoms of different complexity were used. A Monte Carlo (MC) intercomparison exercise with the voxel representations of the physical phantom was launched additionally in September of 2012. The main goals of the action were (1) to investigate the different methodologies for developing MC calibrations that might arise from a complex radiological assessment and (2) to compare individual approaches of the participating laboratories in order to determine international guidance for best practice. The MC exercise consisted of three tasks with increasing difficulty, in order to test the extent of skills needed by the participating laboratory. The first task was to simulate a given detector and a well-defined semi-skull phantom. The second and third tasks presented in this paper-introduced more complex simulations with individual geometry and real detector modelling. The paper provides an overview of the participant's results, analyses of the observed issues concerning tasks two and three, and a general evaluation of the whole project. Highlights: Participants were able to model real detectors and geometries. Three head phantoms with different complexities were used. Typical difference between measured and simulated detection efficiency was less than ±12%. Simulation with voxel phantom is suitable for calibration of partial body counters.